Critical Infrastructure Management and Artificial Intelligence - Vasić, Bojana; Podbregar, Iztok; Dežman, Marina (Management skozi prizmo digitalnega in zelenega prehoda v družbo 5.0, 2025)
Critical infrastructure is the system that is in place for the smooth and stable functioning of countries and societies. It is indisputable that threats and vulnerabilities to the system are an area that needs to be managed, particularly at the national level, comprehensively and sufficiently. Critical infrastructure comprises many interconnected and interdependent vital sectors, and the partial or total failure of just one sector can lead to major social and economic consequences, as well as crises of various kinds. Therefore, the protection, provision, and management of critical infrastructure are of paramount importance for every country. In this paper, we aim to link the role of critical infrastructure in society to elements or trends of change, one of which is undoubtedly artificial intelligence, and critical infrastructure is also exposed to this trend. Like the risks of the past, which stemmed from demographic, economic, technological, or social changes, the risks associated with artificial intelligence are also present in critical infrastructure systems. These are cyber-security risks, issues related to ethics and morality, and elements that we will try to address as comprehensively as possible in this paper.